2016 IEEE 30th International Conference on Advanced Information Networking and Applications (AINA) 2016
DOI: 10.1109/aina.2016.100
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Sensor Management: Extending Sensor Web for Near Real-Time Mobile Sensor Integration in Dynamic Scenarios

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available.Copies of full items can be used for personal research or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Study results also demonstrated that these interoperability standards in combination with data source adapters are important elements of a layer-based architecture because they are able to handle intrinsic heterogeneity of the data sources. This integrated use is performed by building upon and extending previous work that uses adapters for integrating geospatial data [Assis et al 2016]. In other words, those adapters are able to encapsulate the discrepancies and idiosyncrasies of data sources, converting the data to a standardized pattern, and sharing them.…”
Section: Resultsmentioning
confidence: 99%
“…Study results also demonstrated that these interoperability standards in combination with data source adapters are important elements of a layer-based architecture because they are able to handle intrinsic heterogeneity of the data sources. This integrated use is performed by building upon and extending previous work that uses adapters for integrating geospatial data [Assis et al 2016]. In other words, those adapters are able to encapsulate the discrepancies and idiosyncrasies of data sources, converting the data to a standardized pattern, and sharing them.…”
Section: Resultsmentioning
confidence: 99%
“…and local communities must carry out relief activities with a view to building some form of resistance against them, i.e., to enable communities to resist, change or adapt to the conditions if there is a disaster (NORRIS et al, 2008). Traditional data sources have been providing useful information about environmental variables; for example, hydrological stations to measure the water level in riverbeds, weather radars to detect the weather conditions, and rainfall gauges to calculate the volume of rainfall (MANSOURIAN et al, 2006;LEE et al, 2008;MARKOVIC;STANIMIROVIC;STOIMENOV, 2009;HUGHES et al, 2011;ASSIS et al, 2016). These data sources have been supplemented by ordinary volunteers who have been providing valuable information about the current situation in affected areas by means of social media platforms (e.g., Twitter), SMS, participatory platforms (e.g., citizen observatories and mobile apps), and collaborative mapping (e.g., OpenStreetMap) (ERSKINE; GREGG, 2012;DEGROSSI et al, 2014;ALBUQUERQUE et al, 2015).…”
Section: Contextualizationmentioning
confidence: 99%
“…Chapter 2 contains a systematic literature mapping of approaches to integrate dynamically heterogeneous sensors into the Sensor Web (Objective 1). Chapter 3 (ASSIS et al, 2016) was accepted at the 30th IEEE International Conference on Advanced Information Networking and Applications (AINA-2016) and describes a dynamic sensor management component that extends the Sensor Web for near real-time mobile sensor integration in dynamic scenarios (Objective 2). Chapter 4 was accepted at the 35th Brazilian Computer Society Conference (CSBC-2015) (ASSIS et al, 2015a) and 16th Brazilian Symposium on Geoinformatics (GEOINFO-2015) (ASSIS et al, 2015b) and outlines an automated geographical prioritization of social network messages using sensor data stream: an application to floods (Objective 3).…”
Section: Organization Of This Thesismentioning
confidence: 99%